Innovative Leadership by the Principal at the Aisyiyah Bustanul Athfal Bebekan Preschool, a Pilot School: Kepemimpinan Inovatif Kepala Sekolah Pada Sekolah Penggerak di TK Aisyiyah Bustanul Athfal Bebekan - Zakiyyah, Ummu; Hidayatulloh (Indonesian Journal of Innovation Studies, 2026)
General Background: Institutional leadership plays a decisive role in driving organizational adaptation within dynamic educational environments. Specific Background: Early childhood education institutions undergoing government-mandated reforms require structured leadership adaptation to optimize curriculum execution and institutional standards. Knowledge Gap: However, empirical assessments regarding the operationalization and systemic outcome of innovative principal leadership within early childhood Movers School frameworks remain limited. Aims: This qualitative case study evaluates the implementation, operational results, and institutional contributions of innovative principal leadership at TK Aisyiyah Bustanul Athfal Bebekan. Results: Findings reveal that the principal operationalized transformational behaviors by embedding eight specific leadership indicators, successfully advancing curriculum modification, data-driven management, and institutional digitalization. Novelty: This study establishes a concrete multidimensional indicator framework for principal leadership tailored specifically to early childhood educational drive initiatives. Implications: Practically, these results offer an actionable blueprint for early childhood administrators to optimize school quality, technological integration, and stakeholder engagement. Key Findings Highlights Operationalized eight innovative leadership indicators to drive systemic educational reform. Advanced institutional transformation through curriculum integration, data-driven management, and digital technology. Strengthened educational quality, stakeholder collaboration, and overall school ecosystem performance. Keywords: Innovative Leadership, Movers School, Early Childhood Education, Curriculum Innovation, School Digitalization